The impact of websites and social media marketing on the efficiency of e-commerce - Daliborka Blazheska; Natasha Ristovska; Sashko Gramatnikovski (UTMS Journal of Economics, 2022)
Creating websites and social media marketing is an integral part of business activities in companies. The emergence of modern technologies has caused major changes in the operation of companies. Websites and social networks have become extremely popular because they offer many opportunities to companies and users. These are important tools that every company should use in carrying out their marketing activities, because no media can convey information faster than them. Social networks serve companies to build better customer relationships and enable the creation of a recognizable brand. In this paper, special emphasis is placed on the research on how Macedonian companies are aware of the impact of the website and social media marketing in building relationships with consumers and increasing the effectiveness of e-commerce. From the research we can see that the implementation of modern digital technologies is needed as well as the integration of communication and sales channels which are important factors for business success in the market. The concept of increasing the effectiveness of e-commerce is based on the use and support of Internet technologies and directing most of the company's transactions to transactions through the company's website.
Keywords: M30; M13; L26; 330; website; social networks; effectiveness; communication; e-commerce